Smart Hair Machine / Muhammad Aiman Mohd Radzi - Mohd Radzi, Muhammad Aiman (2020)
Smart hair machine is a product which has dual function in order to use it. This product has many advantages compared with other products. Components inside this product have dry and wet sessions. Our product has a great quality and technology that can satisfy our consumers. In this product, we applied an easy way for our customers to dress up themselves. They no need to go to the toilet to make his hair wet but just switch the button and after that can use it. After making it wet, they will continue with drying to perform a hairstyle. Furthermore, we also provide affordable prices with high quality and long lasting materials. We managed to develop this product because to overcome the problem that is being faced by common people. From here, they will simply manage themselves and reduce their energy. They also do not have to worry if there are any problems because we already present a well functioned product. Other than that, we also provide a suitable colour that can attract our customers to buy it.